More than one wife : polygamy and grace - Ntagali, Stanley; Hodgetts, Eileen Enwright ([not indicated] [not indicated], 2011)
What does the Bible say about polygamy? What did Jesus say? How should the church approach the subject of polygamy in the 21st Century? Should polygamists be admitted to the church membership? More than One Wife is an exploration of the Biblical and cultural roots of polygamy and its place in modern African society. Although the authors are firmly in favor of monogamy as the ideal for Christian marriage they urge us to have compassion for the men, women and children trapped in polygamous cultures. Archbishop Stanley Ntagali, Primate of the Church of Uganda, recalls the pain created by the first missionaries in their attempt to impose Western standards on African society which resulted in refusing church membership to polygamists and their wives and children.
Keywords: Polygamy -- Religious aspects -- Christianity; Women -- Uganda; Uganda -- Social conditions